Perceived quality of maternal care and its barriers based on women’s perspective in hospitals of Northwest Ethiopia: a qualitative study - Mekie, Maru; Belachew, Yismaw Yimam; Chanie, Ermias Sisay; Bayih, Wubet Alebachew; Fenta, Setegn Muche; Masresha, Gedefew Abeje; Ferede, Wassie Yazie; Addisu, Dagne (Frontiers in Medicine, 2024)
Background The Sustainable Development Goals (SDGs) in health focus on achieving equity to reduce maternal mortality disparities among subpopulations globally. The goal is to lower the maternal mortality ratio (MMR) to below 70 per 100,000 live births by 2030 for countries with an MMR below 420 in 2010. For those exceeding 420, the target is to keep the MMR below 140 by 2030. This target could not be achieved unless quality maternal health care service is implemented in all health care settings. This study aimed to assess the quality of maternal care and perceived barriers based on women’s perspectives among women who receive delivery services in hospitals of South Gondar Zone, Northwest, Ethiopia. Methods A phenomenological method was implemented to explore women’s perspectives on quality maternal care and its perceived barriers. An in-depth interview (IDI) was used to collect data using a semi-structured in-depth interview guide. The study was conducted from January 1–30, 2021. All in-depth interview notes were translated into meaningful notes. Then notes were organized by coding texts into meaningful elements using open code version 4.03 software. Results The majority (14 in 20) tried to interpret quality care in terms of respect during procedures, providing family support, and timely care. Some (6 in 20) tried to associate quality care with the competency of care providers, the cleanliness of the procedure, and privacy during care. With regards to perceived barriers to quality care, the majority (15 in 20) of the IDI participants agreed that a high caseload, limited drugs, and administrative problems were barriers to providing quality maternal care. Conclusion Participants articulate a multifaceted understanding of quality maternal care that encompasses emotional support, accessibility, cleanliness, timely interventions, and respectful treatment. They also identify significant barriers that stem from facility limitations, provider attitudes and knowledge, and administrative inefficiencies. Addressing these barriers is essential for enhancing the quality of maternal health services.